Effect of cervical sympathetic block on cerebral vasospasm after subarachnoid hemorrhage in rabbits - Chun-jing,He (2013)
PURPOSE: Cerebral vasospasm (CVS) is a major complication after subarachnoid hemorrhage (SAH) induced by the rupture of intracranial aneurysms. The aim of the present study was to investigate the effect and mechanism of cervical sympathetic block on cerebral vasospasm of the rabbits after SAH. METHODS: After successful modeling of cervical sympathetic block, 18 healthy male white rabbits were randomly divided into three groups (n=6), ie, sham operation group (Group A), SAH group (Group B) and SAH with cervical sympathetic block group (Group C). Models of delayed CVS were established by puncturing cisterna magna twice with an injection of autologous arterial blood in Groups B and C. A sham injection of blood through cisterna magna was made in Group A. 0.5 ml saline was injected each time through a catheter for cervical sympathetic block after the first injection of blood three times a day for 3 d in Group B (bilateral alternating). 0.5 ml of 0.25% bupivacaine was injected each time through a catheter for cervical sympathetic block after the first injection of blood three times a day for 7 d in Group B. 2 ml venous blood and cerebrospinal fluid were obtained before (T1), 30 min (T2) and 7 d (T3) after the first injection of blood, respectively, and conserved in a low temperature refrigerator. Basilar artery value at T1, T2 and T3 was measured via cerebral angiography. The degree of damage to nervous system at T1 and T3 was recorded. RESULTS: There was no significant difference in diameter of basilar artery at T1 among three groups. The diameters of basilar artery at T2 and T3 of Groups B and C were all smaller than that in Group A, which was smaller than Group C, with a significant difference. There was no significant difference in NO and NOS in plasma and cerebrospinal fluid among three groups. The NO and NOS contents at T2 and T3 of Groups B and C were all lower than Group A; Group C was higher than Group B, with a significant difference. The nerve function at T3 of Groups B and C were all lower than Group A and that of Group C higher than Group B, with a significant difference. CONCLUSION: Cervical sympathetic block can relieve cerebral vasospasm after subarachnoid hemorrhage and increase NO content and NOS activity in plasma and cerebrospinal fluid to promote neural functional recovery.